Developing Fast, Red-Light Optogenetic Stimulation of Spiral Ganglion Neurons for Future Optical Cochlear Implants - Huet, Antoine Tarquin; Dombrowski, Tobias; Rankovic, Vladan; Thirumalai, Anupriya; Moser, Tobias (Frontiers in Molecular Neuroscience, 2021)
Optogenetic stimulation of type I spiral ganglion neurons (SGNs) promises an alternative to the electrical stimulation by current cochlear implants (CIs) for improved hearing restoration by future optical CIs (oCIs). Most of the efforts in using optogenetic stimulation in the cochlea so far used early postnatal injection of viral vectors carrying blue-light activated channelrhodopsins (ChRs) into the cochlea of mice. However, preparing clinical translation of the oCI requires i) reliable and safe transduction of mature SGNs of further species and ii) use of long-wavelength light to avoid phototoxicity. Here, we employed a fast variant of the red-light activated channelrhodopsin Chrimson (f-Chrimson) and different AAV variants to implement optogenetic SGN stimulation in Mongolian gerbils. We compared early postnatal (p8) and adult (> 8 weeks) AAV administration, employing different protocols for injection of AAV-PHP.B and AAV2/6 into the adult cochlea. Success of the optogenetic manipulation was analyzed by optically evoked auditory brainstem response (oABR) and immunohistochemistry of mid-modiolar cryosections of the cochlea. In order to most efficiently evaluate the immunohistochemical results a semi-automatic procedure to identify transduced cells in confocal images was developed. Our results indicate that the rate of SGN transduction is significantly lower for AAV administration into the adult cochlea compared to early postnatal injection. SGN transduction upon AAV administration into the adult cochlea was largely independent of the chosen viral vector and injection approach. The higher the rate of SGN transduction, the lower were oABR thresholds and the larger were oABR amplitudes. Our results highlight the need to optimize viral vectors and virus administration for efficient optogenetic manipulation of SGNs in the adult cochlea for successful clinical translation of SGN-targeting gene therapy and of the oCI.